Digitalization Islamic Boarding School Management With an Integrated Website Information System: Digitalisasi Pengelolaan Pondok Pesantren Dengan Sistem Informasi Website Terintegrasi - Taufikurrahman; Dhian Satria Yudha Satria; Laqma Dica Fitrani; Muhamad Aris Burhanudin (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Islamic boarding schools in Indonesia, including the Nazhatut Thullab Prajjan Camplong Madura Foundation, face the challenge of digital adaptation in the era of disruption. External communication management still relies on conventional methods, hampering efficiency and transparency. The main problems include limited communication channels with students' guardians, low digital literacy among administrators, scattered data, and the suboptimal use of websites as a medium for socialization and da'wah. To address these issues, this activity proposes the development and implementation of an integrated website with a focus on the message blast feature for mass and rapid communication. The community service was implemented in five stages: a preliminary survey and needs analysis through interviews and direct observation; the design and development of a user-friendly integrated website with attention to data security; planning and preparation of a training program, including the creation of pre- and post-tests to measure knowledge; implementation of training and mentoring on July 19-20, 2025, for 16 Islamic boarding school administrators using presentations, lectures, practice, and discussions; and ongoing monitoring and evaluation. The results of the activity showed significant improvements in administrative efficiency and transparency through a functional website system. Posttest results were consistently significantly higher than pretest results, indicating increased human resource capacity in utilizing information technology. Participants demonstrated optimal technology adoption and were able to operate the website independently.